Influence of Surface Modification Methods on the Topography of Dental Implants by Using Metrological Observation Techniques - Bulutsuz, A. G.; Mercan, C. U.; Karapinar, G.; Katiboglu, A. B.; Lewandowska, M. (POLISH ACAD SCIENCES INST PHYSICS, 2016)
Over the last few decades the use of dental implants has been increasing everyday as a solution for partial or full edentulism. The osseointegration process has to be fully completed to reach a prosthetic phase, so that patient can start to use the dental implants functionally. One of the most important factors affecting osseointegration is the surface properties of dental implants. Surface roughness of dental implant is vital to increase bone anchoring and maintain the biomechanical stability. In addition to successful application of dental implants, rapid osseointegration has also been desired as a favorable situation. It is demonstrated that there is a strong correlation between the successful application and rapid osseointegration of dental implants and the surface morphology and characteristics of dental implants. From this point of view, investigation of the surface morphology of implants has a vital importance for manufacturers. The aim of our study was to evaluate the surface topography and homogeneity of dental implants with different surface modifications by means of 2D and 3D observation methods.
Keywords: TITANIUM IMPLANTS; ROUGHNESS; Physics